Oil exports, non-oil exports and economic growth: time series analysis for Kuwait (1970-2004) - Merza, Ebrahim (Kansas State University, 2007)
Kuwait is an oil-based economy that adopts an export promotion policy as the fundamental strategy for economic growth. The country has experienced remarkable economic growth and high per capita GDP for the last four decades. The export-led growth (ELG) hypothesis has been commonly used to examine the impact of exports on economic growth. Numerous studies support this hypothesis and found evidence that exports have a significant positive relationship with economic growth. However, it is not yet known how effective the ELG hypothesis is in small oil producing country like Kuwait. The central question addressed is whether the ELG hypothesis is valid in the case of Kuwait. This empirical research investigates the relationship of two components of exports (oil exports and non-oil exports) with economic growth by examining the ELG hypothesis using annual time series data for the Kuwaiti economy over the period 1970-2004. The study applies a number of econometric techniques: unit root test, cointegration test, error correction model (ECM), impulse responds function (IRF), and Granger causality test. The results of this dissertation show that all the variables are stationary in the first difference. Moreover, the cointegration test confirms the existence of the long run relationship among the three variables. The Granger test shows bidirectional causality between oil exports and economic growth, and a unidirectional causality from non-oil exports to economic growth. However, the causality results are consistent with the results reported by the ECM.
Keywords: Economics; Economics, General (0501)